Lecturers and postgraduates perception of libraries as promoters of teaching, learning and research in university of Ibadan, Nigeria (2015)
Lecturers and postgraduates are among the users of the university libraries and their perception of the libraries has influence on utilization of the information resources, hence the need for this study. Survey method was adopted for the study and simple random sampling method was used to select sample size of 38 lecturers and 233 postgraduates. Data was collected through a questionnaire complemented by an interview schedule. Results revealed that the overall perception was not favorable as 62% of lecturers and 77.7% of postgraduates indicated that they were not satisfied with the resources and facilities in the library.